Adaptaciones curriculares del área de matemáticas en niños con necesidades especiales no asociadas a la discapacidad de primer año de educación básica de la Escuela Despertar del cantón Quevedo, provincia de Los Ríos - Laje Terán, Geomayra Estefanía (2022)
A person with special abilities is considered to be any human being who temporarily or partially presents a limitation, loss or diminution of their physical, intellectual or sensory capacities to carry out their connatural activities. Considering that people with special abilities are those who need or require a different learning process to develop their skills and abilities; Since these people are vulnerable, they need constant support in their process to be able to find ways to grow and fulfill themselves. There are different types of special abilities, some are detectable from an early age and others are detected during the educational process. When referring to children with special abilities, the focus is on any child who may need help due to a medical, emotional or learning problem; These children who have different special needs in some cases require therapy, medicine, extra help in their educational institution, things that other children do not usually need or need from time to time. For a child with special abilities, life usually presents more challenges, it may be more difficult to carry out normal activities, such as learning to read, add, or if the person has a physical disability, it may be difficult for him or her to move within the school, home, or by the mall. The special capacities can be of organic origin and in many cases the origin of said disability is unknown; The environment can greatly influence the improvement of the problems that arise and the evolution of people with special abilities, thus preventing the appearance of other problems or disorders. Hence the importance of training parents and educators.